Order and Confusion. The Twelfth-Century Choir of the St. Servatius Church in Maastricht - Ashmann, Fred B.P. (Clavis, 2017)
Order and Confusion is the title of a groundbreaking and monumental reconstruction of the twelfth-century choir of St. Servatius Minster in Maastricht, based on its scholarly decoration program - a Gesamtkunstwerk - comprising an altar, reliquary shrine, wall and vault paintings as well as other elements by Fred B.P Ahsmann. The book Order and Confusion elucidates how all key political and ecclesiastic themes of the twelfth century come together in the twelfth-century choir of St. Servatius: the conflict between pope and emperor; various notions of earthly power and heavenly order; and the anticipated end of days of the Sacred History. The Chapter of St. Servatius – having close ties to the emperor – apparently resorted to every visual means available in order to convey its position during this period of tumult, in an era hovering between order and confusion.